(3GdaQbs - (3KGHJ Hf CHj KGHJ SYjO Gdchaj , CHh eMeO,J (B250 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efgG bhd QDHI (B: (3cGdMhJ dG jQhjg TF jdgeg jUHM XeBf hai GdHMQ aeg s
(3BNQgG (B:s
(3BNQ GdehLhO efgG ef GhUGa GdeTi (B: (3hbGd GdCUeYi (B: (3MOKfi HYV Cgd GdYde abGd dg (B: (3hcja YdeJ Pdc ; bGd (B: (3EfgG eTJ bcJaJ hNHJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI ebGHdIs
(3GdfSNI fGbUI ef ChdgG ebOGQ hQbI hGMOIs
(3hcPdc PgH ef CNQgG ebOGQ hQbIs
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B97 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B100 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B248s
Keywords: (3GddZIs